Provosts’ Quality Assurance Strategies and Lecturers’ Job Performance in Colleges of Education in Kwara State, Nigeria - Adeseko Sunday Olaifa; Taofeeq Saadu Issa; Ebunlomo Oreoluwa Olaifa; Johnson Abiodun Medupin; Moses Adeleke Adeoye (Journal of Education Reseach and Evaluation, 2024)
The continuous decline in lecturer performance, especially at Colleges of Education, has raised significant concern among education stakeholders. This research aims to analyze the relationship between the chancellor's quality assurance strategy and the work performance of lecturers in universities of education. This research uses a descriptive survey with a correlational type. The research sample consisted of 285 lecturers. A proportional random sampling technique was used to select the number of respondents. The instrument for data collection is the Chancellor's Quality Assurance Strategy and Lecturer Work Performance Questionnaire (PQASLJPQ). The questionnaire was divided into three sections: section A for demographic data collection; Part B contains matters regarding the chancellor's quality assurance strategy; and Part C has items regarding lecturer work performance on a modified 4-point Likert rating scale. The data collected was analyzed using the mean rating to answer the research questions. Pearson Product Moment Correlation (PPMC) was used to test the research hypothesis at a significance level 0.05. The research results show a significant relationship between the chancellor's quality assurance strategy and lecturers' work performance. This study shows adequate supervision, staff development programs, and stress management can improve teacher performance and school effectiveness. It is recommended that the rector maintain a high professional spirit and moral standards to effectively implement quality assurance strategies and maintain favorable working conditions for lecturers.